Motorcycle Security System using SMS Warning and GPS Tracking - Budi Artono; Tri Lestariningsih; R. Gaguk Pratama Yudha; Arizal Alfan Bachri (Journal of Robotics and Control (JRC), 2020)
Today, technology has been developing rapidly. Various types of technology have been developed and provide a great deal of convenience in human life activities, including security systems. Motorcycles, parked in a park or on the street, are at high risk of being stolen. A security system for Motorcycles with SMS warning and GPS tracking that can prevent theft of a motorcycle is needed. The research aimed to design a security system for motorcycle consisting of a SIM808 GSM Module to send warning messages, and a GPS tracker to provide information in latitude and longitude coordinates to track the stolen motorcycle using Google Maps. GPS Tracker worked by reading the coordinates where the object was located. The tests were carried out by moving and integrating the motorcycle system, and the results could be seen in the coordinate changes, monitored by Google map showing the movement of the motorcycle. The system made was significantly closer to what was planned.